Geochemical and metamorphic record of the amphibolites from the Tuting–Tidding Suture Zone ophiolites, Eastern Himalaya, India: implications for the presence of a dismembered metamorphic sole. (29th May 2021) - Dutt, Amrita; Singh, A Krishnakanta; Srivastava, Rajesh K; Oinam, Govind; Bikramaditya, RK
Abstract: The Tuting–Tidding Suture Zone (TTSZ), exposed along Dibang and Lohit river valleys in Arunachal Himalaya, NE India, is the easternmost continuation of the Indus–Tsangpo Suture Zone (ITSZ) and consists of ophiolites associated with metabasics and carbonates. Amphibolites, existing at the base of the ophiolite complex, were studied using whole-rock, mineral chemical analyses and pressure–temperature ( P - T ) pseudosection modelling to understand their metamorphic and petrogenetic history, and interpret the tectonic environment of their formation. They exhibit two-stage deformation, where D1 is depicted by polymineralic inclusion trails in former melt pools and the main foliation represents D2 . Sub-alkaline tholeiitic character, high-field-strength element (HFSE) ratios and mid-oceanic ridge basalt (MORB) -like rare earth element (REE) patterns with negative Eu anomaly indicate that the protolith of these amphibolites originated in a spreading regime by extensive partial melting of a depleted mantle source at shallow depth. Petrography, mineral chemistry and P - T modelling indicate a three-stage metamorphic history for them. M1 is the prograde ( c.  2.1 GPa, c.  450°C) defined by garnet centre compositions corresponding to the D1 event. The existence of former melts in the samples demarcates the M2 stage (1.4–1.8 GPa, c.  600°C). The rocks later underwent retrogression (M3 : 0.8–1.0 GPa, 480–520°C), which corresponds to the D2 event. These observations suggest that the protolith of the TTSZ amphibolites originated in a mid-oceanic ridge setting, which accreted below a subduction zone where it underwent M1 metamorphism followed by M2 metamorphism, corresponding to partial melting of the rocks. Finally, the M3 event occurred during the obduction phase of the ophiolite complex, where the amphibolites were obducted as the metamorphic sole of the TTSZ ophiolites.